Розробка елементів системи формування та супроводу бібліотеки коміксів - Латишев, О. О. (ХНУРЕ, 2024)
This work is dedicated to a web application that represents a library of comics. Since comics have become one of the most popular forms of literature today – their number is growing every hour and the issue of systematizing them for readers is growing as well. Developing a library of comics as a web application allows solving this problem and also provides a convenient way to interact with it. The main business functions that users of this work will be able to use are reading, organizing comics, and expanding the existing library.
Keywords: бібліотека коміксів; системний супровід; автоматизація процесів